La despedida Española : homenaje a las Brigadas Internacionales, 1938-2008 / [compilador, Manuel Requena Gallego] - Requena Gallego, ManuelAlberti, Rafael (1902-1999) Hernández, Miguel (1910-1942) Neruda, Pablo (1904-1973) Luis, Leopoldo de (1918-2005) Morán, Fernando (1926-) Azaą, Manuel (1880-1940) Negrín, Juan (1892-1956) Ibárruri, Dolores (1895-1989) Machado, Antonio (1875-1939) (España en armas; 13)
Contiene textos de Rafael Alberti, Miguel Hernández, Pablo Neruda, Leopoldo de Luis, Fernando Morán, Manuel Azaą, Juan Negrín, Dolores Ibarruri, Antonio Machado.